HUBUNGAN KETERAMPILAN MEMBACA PEMAHAMAN DENGAN KETERAMPILAN MENULIS TEKS EKSPOSISI SISWA KELAS X SMA NEGERI 1 PULAU PUNJUNG KABUPATEN DHARMASRAYA - Rahmadani, Kurnia; Thahar, Harris Effendi; Tamsin, Andria Catri (Universitas Negeri Padang, 2018)
ABSTRACT This article is written to know the relationship of reading comprehension skill with the skills of writing expositions of student of class X SMA Negeri 1 Pulau Punjung Kabupaten Dharmasraya. The type of this research is quantitative research. The method used in this research is descriptive method which uses correlational research design. The population is the students of class X SMA Negeri 1 Pulau Punjung Kabupaten Dharmasraya which consist of 191 students who are divided into six classes. The samples of this research are 30 students. This research consists of two variables, which are independent variable (reading comprehension skill of the exposition of the class X SMA Negeri 1 Pulau Punjung Kabupaten Dharmasraya) and dependent variable (writing skill of expositions students of SMA Negeri 1 Pulau Punjung Kabupaten Dharmasraya). The research’s results show that for the skill of expository writing is required the comprehension skill of reading expository. From the result of the research, it can be concluded that there is significant relation (meaningful) between the reading comprehension skill with the skills of writing expositions of students class X SMA Negeri 1 Pulau Punjung Kabupaten Dharmasraya on degree of freedom n-1 at significant degree 95 % which the tcount is bigger that ttable, which is 5,652 > 1,70. Kata kunci: membaca pemahaman, menulis teks eksposisi